2009 International Conference on Computational Science and Engineering 2009
DOI: 10.1109/cse.2009.264
|View full text |Cite
|
Sign up to set email alerts
|

Precision Time Synchronization Using IEEE 1588 for Wireless Sensor Networks

Abstract: Wireless sensor networks are evolving from relatively undemanding applications to applications which have stronger requirements. The coordination of distributed entities and events requires time synchronization. Although a number of methods have been studied for WSNs, some applications require high precision time synchronization. Precision time synchronization enables a variety of extensions of applications. The IEEE 1588 precision time protocol (PTP) provides a standard method to synchronize devices in a netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…However, for wireless networks, achieving this tight precision's degree seems more complicated due to many variable factors during communication. A recent work [17] investigated the IEEE1558 performances for wireless sensor networks and the obtained precision is less than 200 nanoseconds. However, [17] cannot be applied directly to our context due to large number of exchanged messages for synchronization.…”
Section: B Mac Protocol Overviewmentioning
confidence: 99%
“…However, for wireless networks, achieving this tight precision's degree seems more complicated due to many variable factors during communication. A recent work [17] investigated the IEEE1558 performances for wireless sensor networks and the obtained precision is less than 200 nanoseconds. However, [17] cannot be applied directly to our context due to large number of exchanged messages for synchronization.…”
Section: B Mac Protocol Overviewmentioning
confidence: 99%
“…But as wireless networks are limited in terms of size, power and complexity, most implementations of the IEEE 1588 are used on wired networks. On this matter, [12] presents experiments and a performance evaluation based on accurate time synchronization with IEEE1588 in WSNs. Results have shown that the synchronization between the master clock and the slave clocks of the network nodes is achieved with an accuracy to a tenth of a microsecond (100ns).…”
Section: A Synchronization Problems and Protocolsmentioning
confidence: 99%
“…To obtain precise time synchronization in WSN, it is necessary that the clock of the processor be controlled by a TCXO (Temperature Compensated Crystal Oscillator) at 37.5MHz [12], which has a 1.5PPM frequency tolerance, in order to reduce the drift rate. For our simulation, the internal clock of each node in the network was implemented with a drift of 1.5 microseconds per second.…”
Section: A Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The IEEE-1588 PTP can be simply described as follows: (1) the slave node timestamps the synchronization message received from the master node, compares it with the actual timestamp stored in the master's follow up message and gets the first time difference between these two timestamps; (2) the slave node timestamps the instant when a delay request message is sent to the master; (3) the master node timestamps the instant at the arrival of the delay request message and sends back a delay response message with the delay request arrival timestamp to the slave node; (4) the slave node gets the second time difference between the two timestamps, averages the first and second time difference and finally synchronizes the two nodes. The detailed description of the IEEE-1588 PTP can be found in [12,14].…”
Section: Ptp Routermentioning
confidence: 99%